Oligomeric epoxide–amine adducts based on 2-amino-N-isopropylacetamide and α-amino-ε-caprolactam: Solubility in presence of cyclodextrin and curing properties - Fischer, Julian; Ritter, Helmut (Beilstein Journal of Organic Chemistry, 2013)
2-Amino-N-isopropylacetamide and α-amino-ε-caprolactam were reacted with glycerol diglycidyl ether to give novel oligomeric thermoresponsive epoxide–amine adducts. These oligomers exhibit a lower critical solution temperature (LCST) behavior in water. The solubility properties were influenced with randomly methylated β-cyclodextrin (RAMEB-CD) and the curing properties of the amine–epoxide mixtures were analyzed by oscillatory rheology and differential scanning calorimetry, whereby significant differences in setting time, viscosity, and stiffness were observed.
Keywords: amino acids; curing properties; cyclodextrin; epoxide–amine oligomers; LCST

(untitled) - Trellenkamp, T.; Ritter, H. (Macromol. Rapid Commun., 2009)

(untitled) - Kretschmann, O.; Choi, S. W.; Miyauchi, M.; Tomatsu, I.; Harada, A.; Ritter, H. (Angew. Chem., Int. Ed., 2006)

(untitled) - Saunders, B. R.; Vincent, B. (Adv. Colloid Interface Sci., 1999)

(untitled) - Schmaljohann, D. (Adv. Drug Delivery Rev., 2006)

(untitled) - Heskins, M.; Guillet, J. E. (J. Macromol. Sci., Part A, 1968)

(untitled) - Ritter, H.; Sadowski, O.; Tepper, E. (Angew. Chem., Int. Ed., 2003)

(untitled) - Ritter, H.; Cheng, J.; Tabatabai, M. (Beilstein J. Org. Chem., 2012)

(untitled) - Maatz, G.; Maciollek, A.; Ritter, H. (Beilstein J. Org. Chem., 2012)

(untitled) - Zhu, J.-L.; Liu, K. L.; Zhang, Z.; Zhang, X.-Z.; Li, J. (Chem. Commun., 2011)

(untitled) - Choi, S.; Munteanu, M.; Ritter, H. (J. Polym. Res., 2009)

(untitled) - Ritter, H.; Tabatabai, M. (Prog. Polym. Sci., 2002)

(untitled) - Wenz, G. (Angew. Chem., Int. Ed. Engl., 1994)

(untitled) - Szejtli, J. (J. Mater. Chem., 1997)

(untitled) - Wang, J.; Li, S.; Ye, L.; Zhang, A.-Y.; Feng, Z.-G. (Macromol. Rapid Commun., 2012)

(untitled) - Klee, J.; Hörhold, H.-H.; Schütz, H. (Acta Polym., 1987)

Polymeric Materials Encyclopedia - Klee, J.; Hörhold, H.-H. (Epoxide-amine addition polymers, linear, 1996)

(untitled) - Ramesh, D.; Vasudevan, T. (Prog. Org. Coat., 2009)

(untitled) - Swier, S.; Van Mele, B. (Polymer, 2003)

(untitled) - Chen, J.-L.; Chang, F.-C. (Polymer, 2001)

(untitled) - Liu, X.; Wang, Y.; Cao, Y.; Yadama, V.; Xian, M.; Zhang, J. (Carbohydr. Polym., 2011)

(untitled) - Biagini, S. C. G.; Gibsoné Thomas, S. E.; Keen, S. P. (J. Chem. Soc., Perkin Trans. 1, 1998)

WO Patent - Frost, J. W. (Synthesis of caprolactam from lysine, 2005)

(untitled) - Philippe, C.; Milcent, T.; Crousse, B.; Bonnet-Delpon, D. (Org. Biomol. Chem., 2009)

(untitled) - Mondrzyk, A.; Mondrzik, B.; Gingter, S.; Ritter, H. (Beilstein J. Org. Chem., 2012)

(untitled) - Obels, D.; Ritter, H. (Macromol. Rapid Commun., 2013)